Gambaran Kejadian Burnout Pada Perawat Di RSUD Ungaran - Mona Saparwati; Raharjo Apriatmoko (Pro Health Jurnal Ilmiah Kesehatan, 2020)
Complexity nurses tasks can become a heavy burden for nurses in carrying out nursing services to patients. Nurses are likely to become stressed. The inability of individuals coping with prolonged work stress will cause individuals to experience burnout. So in the end nursing burnout will affect to patient satisfaction. The purpose of this research to find out the description of nursing burnout at RSUD Ungaran. This research was conducted with a descriptive analytic strategy. The research population was nurses at RSUD Ungaran with total of 172 people, and 63 respondents was selected as samples by using proportional random sampling technique. The results show that the majority of respondents experience nursing burnout in mild category as many as 32 respondents with 50,8 %. But there are 17 respondents included in the weight category. The results of this study are expected to be the basis for nurses, hospitals and nursing education institutions to pay attention to burnout events. Respondents who are categorized as experiencing high burnout events are expected to immediately carry out further examinations of health services so that they can be handled.